2019
DOI: 10.1186/s12879-019-4524-z
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of hepatitis C virus in Germany: modelling the cost-effectiveness of HCV screening strategies

Abstract: BackgroundChronic hepatitis C is a major public health burden. With new interferon-free direct-acting agents (showing sustained viral response rates of more than 98%), elimination of HCV seems feasible for the first time. However, as HCV infection often remains undiagnosed, screening is crucial for improving health outcomes of HCV-patients. Our aim was to assess the long-term cost-effectiveness of a nationwide screening strategy in Germany.MethodsWe used a Markov cohort model to simulate disease progression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
2
17
0
2
Order By: Relevance
“…Neither of the two treatment groups showed any relevant adverse events. While some bigger studies may have found even higher SVR12-rates, our findings mainly concur with current literature and support the recommendations of broad access to DAA treatment, especially for high-risk populations [ 12 , 17 20 , 22 , 37 , 38 , 44 , 45 , 55 , 56 ]. Still, bigger sample sizes will be needed to validate our results.…”
Section: Discussionsupporting
confidence: 91%
“…Neither of the two treatment groups showed any relevant adverse events. While some bigger studies may have found even higher SVR12-rates, our findings mainly concur with current literature and support the recommendations of broad access to DAA treatment, especially for high-risk populations [ 12 , 17 20 , 22 , 37 , 38 , 44 , 45 , 55 , 56 ]. Still, bigger sample sizes will be needed to validate our results.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have estimated the cost‐effectiveness of enhancing HCV screening in MSM. Firstly, two studies using models that do not account for dynamic HCV transmission showed it was cost‐saving to undertake one‐time screening among HIV‐positive MSM in Germany, 47 and cost‐effective (<€10,000/QALY) to undertaken one‐time or yearly screening among all MSM in Belgium 48 . Otherwise, a dynamic transmission modelling analysis from Netherlands 49 and another model analysis incorporating incidence and reinfection from the USA 50 have shown it was cost‐effective or cost‐saving to undertake screening and/or treatment interventions among HIV‐diagnosed MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, research on hepatitis C progression has been conducted by using Markov chains over the natural history of the disease [42], published by Salomon et. al [1,43], with estimates on the disease progression, associated costs and the number of patients infected with HCV, by age and gender [44][45][46].…”
Section: Discussionmentioning
confidence: 99%